(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The complexes of Co(II), Cu(II) and Ni(II) were synthesized by using schiff base – azo as a ligand, which were prepared under this study by the reaction between the Schiff base diazonium salt and the imidazole derevitive. They were characterized by element analysis, FTIR spectroscopy and UV.VIS. spectroscopy. Their electric conductivity and magnetic features were determined. Their stepwise and overall stability constants and their thermodynamic data ( , and ) were determined. The results showed that all the complexes have paramagnetic features and all of them have good conductivity. The formula of the complexes under this paper were suggested by using the mole ratio method which lead to the formation of (1 : 2) metal : ligand formula for all the complexes. In all the complexes the coordinated sites was through N atoms of the azo groups and N atom of the imidazol ring. The suggested geometrical shapes of the complexes was the octahedral shape due to the ( d2sp3 ) hybridization. Their stepwise stability constants were determined, it was found that for all the complexes they were increased toward the addition of ligand that because of the chelate effect. Their overall stability constants were determined, it was found that for all the complexes were high that because of the chelate effect. Their thermodynamic functions ( , and ) were had negative value, that refer to good stability for the complexes and these results were satisfied with the spontaneous reaction and high stability complexes.